(untitled) (Historia, 2023)
Two South African professional women were early advocates of cannabis decriminalisation during the second half of the twentieth century. Frances Ames (1920-2002) was a neurologist and psychiatrist based at the Medical School of the University of Cape Town. Helen Suzman (1917-2009) represented the Progressive Party for 36 years as an opposition member of parliament. This article documents their individual – later allied – activities and arguments, initially in relation to National Party (apartheid) drug control measures and then into the democratic era of the African National Congress. A social history approach reveals continuities and changes in the cannabis policy rationales of successive governments and the challenges made to these policies.